Integrated Differentiated Learning Social-Emotional Competence: An Innovative Solution to Numeracy Skills - Gunawan, Gunawan; Pertiwi, Budi Wahyu; Ferdianto, Ferry; Akhsani, Lukmanul (JTAM (Jurnal Teori dan Aplikasi Matematika), 2025)
A crucial aspect in various disciplines is numeracy skills. The purpose of the study was to determine the difference in the average social-emotional competence and numeracy skills of students before and after the implementation of differentiated learning that integrated social-emotional competence. The research was conducted at SMP Negeri Satu Atap 1 Cimanggu, Cilacap. The sample in this study was selected using the saturated slicing technique involving 22 grade VIII students. The type of research is an experimental study that uses a pre-experimental design with a one-group pre-test post-test method. The data collection techniques used include observation, tests, and questionnaires. There are 20 questions in the questionnaire. Data analysis was carried out quantitatively using paired sample t-tests and descriptive statistics. Before conducting the analysis, a prerequisite test was carried out using a normality test to test the distribution of data. The results of the study showed that the numeracy skills had a significance value of 0.200 (>0.05) and the social-emotional competence had a significance value of 0.11 (>0.05) which showed that the data was normally distributed. The results of the analysis showed that the value of the t-test of numeracy was 49.423 (t-test > ttable), with a significance value (2-tailed) < 0.05 (0.00 < 0.05). For KSE, the statistical value of the t-test was 27.54 with a very small p-value (5.75×10⁻¹⁸) indicating that there is a significant difference in the average value of numeracy skills and KSE before and after the implementation of integrated differentiation learning KSE. Integrated differentiation learning KSE can be applied to improve numeracy skills. The results of this study can be used as a solution to overcome the low mathematical numeracy skills of students.